Religious Moderation Based on Local Wisdom: (Semiotika Analysis of Roland Barthes in the Novel Hati Suhita by Khilma Anis) - Puji Laksono (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
Religious moderation is a perspective, behavior and attitude that always chooses a position in the middle, is always based on justice, and does not take an extreme position in religious practice. four indicators of religious moderation, namely tolerance, national commitment, non-violence, and acceptance of tradition. In the final indicator, namely acceptance of tradition can be the key to building a paradigm and attitude of religious moderation with a local cultural approach. Religious moderation based on local wisdom is interesting to study. For this reason, researchers analyzed a novel entitled "Hati Suhita" written by Khilma Anis, which carries the collaboration of Javanese and Islamic culture. This research uses a qualitative type of literature study with a semiotic approach. The semiotic analysis knife in this research uses Roland Barthes' semiotics. The results of this research concluded that; (1). There are myths about religious moderation based on local wisdom. These myths include; a). Pre-Islamic culture can still be practiced with adjustments to Islamic teachings. b). Wisdom advice from local traditions can be used as guidance for life while remaining guided by Allah SWT. c). The holy and wise figures in wayang stories can be used as role models, with daily practices according to Islamic teachings. d). A Muslim's name does not have to be Arabic only, but can be paired with a local name that has a good meaning. Then (2). There is an attitude of religious moderation based on local wisdom which is demonstrated by existing myths, namely the value of tawassuth, namely taking the middle path, and tawazun, namely balance between the intersection of Javanese and Islamic culture. This is in accordance with the concept of religious moderation as a perspective, behavior and attitude that always chooses a position in the middle, is always based on justice, and does not take an extreme position in religious practice.